X-ray diffraction studies and dielectric properties of Ni doped Mg ferrites. (June 2018) - Chavan, Pradeep; Naik, L.R.
Abstract: The ferrites with general formula Nix Mg1-x Fe2 O4 (x varies from 0.0 to 0.5) was synthesized by solid state reaction method. The presence of single phase cubic spinel structure of the ferrites without any impurities was confirmed by powder X-ray diffraction measurement. The crystallite size of ferrite materials was estimated by using Scherer formula and is found to be increased in the range from 0.930 μm to 1.04 μm. The lattice constant of ferrites increases with increase in the concentration of nickel and found in the range from 8.332 Å to 8.375 Å. To understand the conduction mechanism, AC conductivity was determined from the data of dielectric constant and dielectric loss. The increase of AC conductivity with increase in applied frequency was due to the conduction mechanism of ferrites which can be explained based on the hopping of charge carriers between Fe 2+ and Fe 3+ on octahedral sites. Highlights: Ferrites synthesized by solid state reaction method. Ferrites generated great interest due to their technical applications. Ferrites have applications in drug delivery, Hyperthermia treatment. Dielectric properties of ferrites have been studied.